Algorithm for Pillar Stability Assessment Based on the Interaction Principle - Mihaela TODERAS (Engineering Research: Perspectives on Recent Advances Vol. 5, 2025)
The room-and-pillar mining method is a prevalent technique for extracting rock salt, potash, and magnesium salt deposits. This method creates a network of rooms (excavated areas) and pillars (supporting columns), requiring careful optimization of their dimensions and the surrounding rock mass properties for each unique geological setting. Because pillars bear the highest loads, their dimensions are typically the primary focus of the design process, influencing the dimensions of the rooms and other system components. Specifically, for deep salt mining using square pillars, optimizing the system involves four key steps: (1) determining the in situ stress state (the stress field in the undisturbed rock mass); (2) analyzing the secondary stress distribution within the pillars, both qualitatively and quantitatively (how the stress changes after excavation); (3) assessing the load-bearing capacity of the pillars (how much weight they can support); and (4) determining the appropriate pillar dimensions (size and shape). Several analytical and numerical approaches can be used to address these challenges. These include: limit equilibrium methods, which consider the effective stress in the pillars; continuum mechanics, which uses analytical models to evaluate stress and deformation in pillars and floors; and numerical methods, such as finite element analysis, often validated with laboratory and field measurements. A proposed methodology, based on the principle of pillar-room-salt mass interaction, offers an analytical approach to determining the stability of deep, dry rock salt mining operations. This method calculates the secondary stress and deformation within the pillars, accounting for salt’s time-dependent deformation (rheological behavior), changes in pillar geometry during extraction, and the specific extraction method employed. This analytical approach can be adapted for use in other mining applications that utilize the room-and-pillar method.